الأحكام العامة لنزع الأعضاء والأنسجة البشرية من جثث الموتى وفقا لقانون الصحة الجزائري لسنة 2018 - زهدور، أشواق (مركز البحث وتطوير الموارد البشرية - رماح, 2021)
يعد الحق بالتكامل الجسدي أحد الحقوق الجوهرية للشخص ويستمر هذا الحق حتى بعد وفاته إذ أن حماية حق الإنسان في تكامل جثته ومعصوميتها وحرمتها أكدته مختلف التشريعات الوضعية غير أنه ونظرا للأعمال الطبية والجراحية المستحدثة فقد أجازت مختلف التشريعات الاستخدام العلاجي للجثث الآدمية وفقا لشروط وضوابط قانونية ومنها المشرع الجزائري الذي نظم مسألة نزع الأعضاء والأنسجة البشرية من جثث الموتى وزرعها في أجسام الأشخاص الأحياء الذين هم في حاجة إليها في قانون الصحة الجزائري رقم 18-11.
The right to physical integration is one of the fundamental rights of a person. This right is maintained even after his death. The protection of the right to the integrity of a person's corpse, its womb and its deprivation has been affirmed in various positive legislation. However, in view of the medical and surgical work that has been developed, the various laws have permitted the therapeutic use of human bodies in accordance with legal conditions and regulations, including the Algerian legislature, which has regulated the removal of human organs and tissues from the bodies of the dead and their implantation into the bodies of living persons in need in Algerian Health law No. 18-11.
Keywords: الموت -- حقوق الإنسان -- الحق في التكامل الجسدي -- نزع الأعضاء البشرية -- نزع الأنسجة البشرية -- الحماية القانونية -- قانون الصحة الجزائري